THE EFFECT OF BUSINESS RISK AND FIRM SIZE ON FIRM VALUE WITH DEBT POLICY AS INTERVENING VARIABLE - Bandanuji, Akhmad; Khoiruddin, Moh. (Management Analysis Journal, 2020)
This study aims to determine the effect of business risk and firm size on firm value with debt policy as intervening variable. The population used in this study are property and real estate companies listed on Indonesia Stock Exchange (BEI) during 2014-2018. Sample determination was done by purposive sampling method. Methods of data analysis using multiple linear regression analysis and path analysis. The results showed that business risk negatively affect the debt policy, while firm size has a positive effect on debt policy. Business risk negatively affects firm values while firm size and debt policy have a positive effect on firm value. Debt policy is only able to mediate the impact of business risk on corporate value